2015
DOI: 10.1586/14787210.2015.1007045
|View full text |Cite
|
Sign up to set email alerts
|

Implications and emerging control strategies for ventilator-associated infections

Abstract: Ventilator-associated pneumonia (VAP) remains a major burden to the healthcare system and intubated patients in intensive care units. In fact, VAP is responsible for at least 50% of prescribed antibiotics to patients who need mechanical ventilation. One of the factors contributing to VAP pathogenesis is believed to be rapid colonization of biofilm-forming pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus on the surface of inserted endotracheal tubes. These biofilms serve as a protective enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…Therefore, a precision medicine is urgently required for vulnerable patients to avoid potential life-threatening infections. Recently, developing biofilm inhibitors has become a priority compared with biofilm disruption due to the advantage provided by preventing subsequent dispersion of cells that may have acquired drug resistance 10 11 12 . Although biofilm control by drug targeting has become a high priority objective 7 13 , marine microbes as a source of novel chemical entities remain relatively underexplored 14 15 .…”
mentioning
confidence: 99%
“…Therefore, a precision medicine is urgently required for vulnerable patients to avoid potential life-threatening infections. Recently, developing biofilm inhibitors has become a priority compared with biofilm disruption due to the advantage provided by preventing subsequent dispersion of cells that may have acquired drug resistance 10 11 12 . Although biofilm control by drug targeting has become a high priority objective 7 13 , marine microbes as a source of novel chemical entities remain relatively underexplored 14 15 .…”
mentioning
confidence: 99%
“…Bacteria or fungi that can form biofilms are possibly morphic and can germinate on surfaces such as medical devices, endotracheal tubes and tracheostomy tubes [13,14]. It has been observed that biofilms are dependent on the fabricated material of such devices [15]. Biofilms cause serious diseases and are a cause of worry for patients with severe respiratory diseases like CF and chronic obstructive pulmonary disease (COPD) [16].…”
Section: Biofilms: Formation Multidrug-resistant Properties and Preventionmentioning
confidence: 99%
“…Indwelling central venous catheters (CVCs) are routinely used to administer medications, blood products, and nutritional fluids to patients, for both temporary and long-term use . The clean surfaces of newly implanted catheters are highly susceptible to microbial colonization. The exopolysaccharide component of the matrix impairs antibiotic penetration , and provides a barrier against phagocytosis by host immune cells . Within biofilms, microbes are up to 1000 times more tolerant to antimicrobials than planktonic cells. ,,, As a result, device-related biofilm infections are difficult to treat using systemic antibiotics and often require device extraction and replacement.…”
Section: Introductionmentioning
confidence: 99%